Contextualizing neuro-collaborations: reflections on a transdisciplinary fMRI lie detection experiment - Littlefield, Melissa M.; Fitzgerald, Des; Knudsen, Kasper; Tonks, James; Dietz, Martin (Frontiers in Human Neuroscience, 2014)
Recent neuroscience initiatives (including the E.U.’s Human Brain Project and the U.S.’s BRAIN Initiative) have reinvigorated discussions about the possibilities for transdisciplinary collaboration between the neurosciences, the social sciences, and the humanities. As STS scholars have argued for decades, however, such inter- and transdisciplinary collaborations are potentially fraught with tensions between researchers. This essay build on such claims by arguing that the tensions of transdisciplinary research also exist within researchers’ own experiences of working between disciplines – a phenomenon that we call ‘Disciplinary Double Consciousness’ (DDC). Building on previous work that has characterized similar spaces (and especially on the Critical Neuroscience literature), we argue that ‘neuro-collaborations’ inevitably engage researchers in DDC – a phenomenon that allows us to explore the useful dissonance that researchers can experience when working between a “home” discipline and a secondary discipline. Our case study is a five-year case study in fMRI lie detection involving a transdisciplinary research team made up of social scientists, a neuroscientist, and a humanist. In addition to theorizing neuro-collaborations from the inside-out, this essay presents practical suggestions for developing transdisciplinary infrastructures that could support future neuro-collaborations.